CLINICAL AND STATISTICAL ANALYSIS OF COMBINED INJURIES OF THE NOSE AND PARANASAL SINUSES - Bakiyeva SH.X.; Karimberdiyev B.I; Djurayev J.A. (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This study presents a clinical and statistical analysis of 140 patients with combined injuries of the nose and paranasal sinuses treated at a multidisciplinary clinic. The study evaluates demographic characteristics, causes of injury, types of trauma, diagnostic methods, and treatment outcomes. The results indicate that such injuries are more common among males of working age. Domestic trauma and road traffic accidents were identified as the leading causes. The findings highlight the importance of timely diagnosis and appropriate surgical management in reducing complications.